Features of the community–acquired pneumonia in a child with Kasabach-Merritt syndrome: case-report and mini-review - Oksana BOYARCHUK; Andrii CHORNOMYDZ; Iryna CHORNOMYDZ (Archives of the Balkan Medical Union, 2019)
Introduction. The Kasabach-Merritt syndrome is a rare and severe disease that occurs in children in the presence of a large-sized hemangioma, accompanied by coagulation disorders. This disease complicates the course of many somatic diseases in children, including community-acquired pneumonia, due to the clotting disorder.